Effects of Reformer training on the quality of life and functional balance in an acute stroke patient: A case report (Indian Journal of Case Reports, 2020)
Pilates is a form of exercise that can be used in stroke rehabilitation to improve gait and balance impairments along with their strength, posture, and quality of life (QoL). The purpose of this case report was to document the effectiveness of using the Pilates reformer to describe the outcomes of an 8-week program on the functional balance and the QoL in an individual with acute stroke. The QoL of the subject was assessed using the stroke-specific QoL scale, and the functional balance was measured using the mini BEST scale both at the baseline and after the end of 8 weeks after exercising on the Reformer. The comparison of the test results before and after 8 weeks suggests that there was an improvement in the balance and the QoL in the patient. Many studies are available suggesting the significance of mat Pilates on stroke patients. However, this case report asserts the significant effects of using a Reformer on an acute stroke patient.